1987
DOI: 10.1083/jcb.104.2.343
|View full text |Cite
|
Sign up to set email alerts
|

Membrane glycoproteins involved in neurite fasciculation.

Abstract: Abstract. Lectin affinity chromatography combined with mAb production was used to identify chick neural cell surface molecules related to L1 antigen, a mouse neural glycoprotein implicated in cell-cell adhesion (Rathjen, E G., and M. Schachner, 1984, EMBO (Eur. MoL Biol. Organ.)J., 3:1-10).A glycoprotein, G4 antigen, isolated by mAb G4 from adult chick brain is described which comprises a major 135-kD component, a minor doublet at 190 kD, and diffusely migrating bands at 80 and 65 kD in SDS PAGE. This molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(187 citation statements)
references
References 44 publications
9
177
0
1
Order By: Relevance
“…2B), a marker that preferentially detects differentiating layered RGCs. 46 Therefore, the majority of the p27 Kip1 -positive cells present in the retina at this stage are differentiating neurons localized in the ganglion cell layer (GCL), as previously described by ref. 47 .…”
Section: Resultsmentioning
confidence: 99%
“…2B), a marker that preferentially detects differentiating layered RGCs. 46 Therefore, the majority of the p27 Kip1 -positive cells present in the retina at this stage are differentiating neurons localized in the ganglion cell layer (GCL), as previously described by ref. 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the many cues that guide the axons of embryonic neurons to their proper destinations, axon fasciculation is an important developmental mechanism. The cell adhesion molecules (CAMs) involved in neurite fasciculation 43,44 include neural cell adhesion molecule (N-CAM) and NGF-inducible large external glycoprotein in the rat, neuron-glial cell adhesion molecule, G4, and 8D9 in the chicken, and L1 in the mouse. The role of CAMs on a given axon is to promote the extension of other neurites along this axon that, in turn, produces fasciculated axons.…”
Section: Discussionmentioning
confidence: 99%
“…We next investigated growth of tectobulbar axons on affinity-purified G4 protein (Rathjen et al, 1987), since previous investigations have shown that G4 is expressed on tectobulbar axons in vivo and in vitro (Kröger and Schwarz, 1990). Retinal axons, whose ability to extend on G4 has already been described (Lagenaur and Lemmon, 1987), were used as controls.…”
Section: Substrate Specificities Of Retinal and Tectobulbar Axonsmentioning
confidence: 99%
“…The nitrocellulose was coated for 2 hr with 40 111 of laminin (1 mg/mi in PBS; LY. labs, San Mateo, CA) or affinity-purified G4 (0.3 mg/mi in carbonate buffer; Rathjen et al, 1987). The drops were spread until they covered a surface of approximately 0.5 cm'.…”
Section: Explant Culturesmentioning
confidence: 99%
See 1 more Smart Citation